Outcome following surgery to treat septic peritonitis in 95 cats in the United Kingdom. (17th May 2021) - Anderson, T.; Beever, L.; Hall, J.; Moores, A.; Llanos, C.; Adams, R.; Meakin, L.; Coppola, M.; Bowlt‐Blacklock, K.; Holmes, M. A.; Barnes, D.
Abstract : Objectives: To review the cause, management and outcome in cats with septic peritonitis within the United Kingdom (2008 to 2018) and to identify if previously identified prognostic factors were associated with survival in this population. Materials and Methods: Clinical records from 10 referral hospitals in United Kingdom were reviewed. Data collected included signalment, clinicopathological data and management techniques. Serum albumin, glucose, lactate and ionised calcium concentration; presence of intraoperative hypotension and correct empirical antibiosis were analysed via logistic regression for association with survival. Results: Ninety‐five cats were included. The overall survival rate was 66%. Lethargy (89%) and anorexia (75%) were the most common clinical signs, with abdominal pain and vomiting in 44% and 27% of cases, respectively. Gastro‐intestinal leakage was the most common source of contamination. The presence of an abdominal mass on clinical examination was not strongly predictive of the presence of neoplasia on histology and did not confer a worse prognosis. Cats presenting with dehiscence of a previous enterotomy/enterectomy did not have a worse prognosis than those presenting with other aetologies. Intraoperative hypotension (adjusted odds ratio 0.173, 95% confidence intervals 0.034 to 0.866, P=0.033) was associated with non‐survival. Cats that survived beyond 1 day postoperatively had an improved likelihood of survival (87.5%). All cats that survived beyond 6 days were successfully discharged. Clinical Significance: This study describes the largest group of cats with septic peritonitis with an overall survival rate of 66%. The presence of an abdominal mass on clinical examination or having dehiscence of a previous gastrointestinal surgery did not confer a worse prognosis.